Crowdfunding : Alternative Financing for Entrepreneurs - BOUZIANI, Lamya; AZEGAGH, Jalal (Revue du contrôle, de la comptabilité et de l’audit, 2024)
The article thoroughly examines the evolution and growing impact of crowdfunding as an alternative source of funding for entrepreneurs. By shedding light on key entrepreneurship concepts and exploring the deep motivations that drive individuals to choose this path, the article provides a solid foundation for understanding the context in which crowdfunding thrives. By delving into various forms of crowdfunding, such as donation, reward, loan, and investment, as well as the processes involved in each modality, it offers a comprehensive overview of this rapidly expanding phenomenon. Additionally, by analyzing the key success factors that determine the effectiveness of crowdfunding campaigns, the article enlightens entrepreneurs on best practices to maximize their chances of success. However, it does not merely highlight the positive aspects of crowdfunding; it also explores the challenges and obstacles faced by entrepreneurs. By providing a balanced and in-depth analysis of these different aspects, the article offers readers a holistic understanding of the crucial role that crowdfunding plays in supporting entrepreneurship and promoting economic innovation. Keywords: Crowdfunding; entrepreneur; entrepreneurship; alternative financing; motivations; key success factors.